K. HEMMERLE’S PHILOSOPHICAL PHENOMENOLOGY OF THE SACRED - M. A. PYLAJEW (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2009)
During the second half of the twentieth century, a new Catholic system of theological thought appeared together and separate from certain concepts regarding religious phenomenology. This was associated with the philosophical phenomenology of the sacred. It came about as a result of the phenomenological ontology of M. Heidegger. The most profound evaluation of the philosophical phenomenology of the sacred comes from the pen of the German Catholic thinker K. Hemmerle. This type of reasoning opened new perspectives in concieving the sacre